DINAMIKA SOSIAL DAN BUDAYA MASYARAKAT BADUY DALAM MENGELOLA HUTAN DAN LINGKUNGAN - Senoaji, Gunggung (Bumi Lestari; Vol 10 No 2 (2010), 2010)
Baduy community is a Sundanese ethnic isolating themselves around Kendeng Mountains, South Banten. They occupy an area about 5101.8 hectares of land in which the property rights were granted from the government. The people strictly adhere to their customary rules and norms. The increase of population has resulted in changes in social and cultural aspect of this community. Hence, this study aimed to investigate social and cultural dynamics of Baduy community in managing its forests and environments. The technique of Partisipatory Rural Apraisal surveys were employed in the study. Data were collected by conducting participating observations and open in-depth interviews in the Kanekes Village, Leuwidamar, Lebak, Banten. The results showed that there have been some dynamic changes in terms of social and cultural of the community in managing their forests and environment. These changes were believed to be initiated by the decrease of availability of cultivated areas due to the population growth. The Baduy community started adjusting their ways of life in order to survive. Customary rules (pikukuh karuhun) which were originally applicable to all people have been shifting. The evidence was clear from the obvious differences in the life of the people of Baduy-Luar and Baduy-Dalam. There has been, for example, an alteration in the people’s status in the society. It was all community members that have to obey the pikukuh karuhun rules. However, currently Baduy-Luar community has also been helping to maintain the persistence of Baduy-Dalam’s pikukuh karuhun. Basic rules that must be followed by Baduy’s people include farming procedures and post-productions, the treatment to the forest and environment, and the implementation of the Sunda Wiwitan pillars. These customary rules were absolutely compulsory for the Baduy-Dalam’s people. However, there are some exceptions for Baduy-Luar community members, particularly in relations to fulfilling their daily life necessities. Some socio-cultural changes in the life of Baduy’s people include dress codes, the use of manufactured goods, land preparation methods, variety of cultivated crops and plantations, the use of transportation means, and the design of residential buildings.
Keywords: Baduy community, forests and environments, social and cultural dynamics